Hotel guest preferences of in-room technology amenities. (3rd May 2016) - Bilgihan, Anil; Smith, Scott; Ricci, Peter; Bujisic, Milos
Abstract : Purpose: Advances in technology and in subsequent guest-related amenities have the potential to improve the guest experience and also increase both guestroom revenues and ancillary room revenues. Innovative technologies will be one of the prime differentiators of hotel companies in the twenty-first century. However, it is important for hoteliers to answer questions such as which technology amenities do their guests desire when choosing overnight accommodations? Further, what are the importance levels assigned by guests of these various technology amenities? This study aims to answer the question of how leisure travelers may differ or be similar to business travelers with regard to in-room technology amenities. Design/methodology/approach: The target population of this study consisted of 2, 500 US residents whose email addresses were randomly drawn from a national database company. A series of t -tests and ANOVA were conducted to answer the research questions. Findings: High-speed internet access and guest device connectivity were perceived more important by business travelers than by leisure travelers. Research limitations/implications: Recognizing guests' technology needs and answering those needs are important for hotel operators to remain competitive. While some segments perceive more value in certain technologies, for others it might be an indifferent amenity. Practical implications: The amount of time guests spend in their rooms directly correlates to increased revenues from in-room dining, in-room amenities offered and, in general, all pay-for-use products and services such as the internet and movies. Therefore, with the right assortment and offering of technology amenities, hotels will increase their revenues from these ancillary revenues. Moreover, a hotel property with the right mixture of desired in-room amenities and services can charge higher rates for their guestroom sales. Originality/value: The results of this study provide insights into the changing attitudes toward in-room entertainment technology that many hotel developers should take note of.